In Praise of the Prophet: Forms of Piety as Reflected in Arabic Literature - Weinrich, Ines (Ergon-Verlag, 2022)
This volume provides a contribution to Arabic literary history from an exceptional perspective. It examines the literary expression of veneration of the prophet Muhammad, primarily the hitherto little researched field of praise poetry to the prophet (al-madīḥ an-nabawī) and its diverse manifestations – as a personal form of piety, literary contest, or musical performance. Alongside emulations of the well-known 13th-century Mantle Ode, the volume treats strophic poetry in the vernacular, mawlid texts, prophetic praise in the maqāma genre and in the Moroccan musical tradition (nūba), as well as prayer books and letters to the Prophet's tomb. Many influential works and poets are presented for the first time in Western research.